Community Readiness for Childhood Obesity Prevention: Findings From a Statewide Assessment in Georgia. (January 2016) - Sheldon, Erica; Lyn, Rodney; Bracci, Laura; Ann Phillips, Mary
As investments are made to engage communities in childhood obesity prevention efforts, an approach to better understand local communities' readiness to implement evidence-based strategies is needed. The Community Readiness Model (CRM) was used to assess the readiness of 15 communities in Georgia actively working to prevent childhood obesity. Seventy-nine key informant interviews were conducted assessing six dimensions of readiness. Data were analyzed and scored using the CRM protocol. Overall community readiness scores ranged from 2.8 to 5.1 on a 9-point scale. The mean readiness score, 4.3 ( SD = 0.5) corresponds with a preplanning level of readiness. Findings suggest that communities are recognizing the problem, organizing stakeholders, and beginning to develop solutions. There is a need for funders to match their community-based funding initiatives with the readiness levels of the communities being supported. Communities should focus their attention to the six dimensions of readiness while utilizing evidence-based frameworks and guidance on prevention.